"Nyabis" Local Wisdom as A Values Transformation in Governance at Pondok Pesantren Salafiyah Raudlatul Ulum Sumberwringin Jember - Fauzan, Fauzan; Aladist, Irham; Mustafidah, Ayyu Ainin (IJIBS, 2023)
The "nyabis" or "silaturahmi" culture is part of Indonesian people's social and religious culture, especially by the santri or Islamic boarding school students. Nyabis activities are carried out to show respect and respect for fellow students who are more senior, scholars or teachers at Islamic boarding schools, as well as community leaders visiting Islamic boarding schools. Nyabis culture in Islamic boarding schools has an essential role in the life of students. Nyabis activities can strengthen social relations between students and scholars or teachers at Islamic boarding schools to create a harmonious and conducive atmosphere within the Islamic boarding school. In addition, nyabis are also a means for sharing knowledge and experiences among students. Nyabis activities are usually carried out at certain times, such as when guests visit Islamic boarding schools or on certain days, such as holidays or important Islamic commemorations. In some pesantren, nyabis activities are carried out on a scheduled or routine basis on certain days of the week. The nyabis culture in Islamic boarding schools shows the importance of social and religious values in the life of santri. Nyabis activities can also be a means to strengthen social and cultural networks in society, as well as to enhance brotherhood among Muslims. Therefore, Nyabis culture must be preserved as part of local wisdom and Indonesian cultural values. Thus, in this study, the researchers tried to unravel the problem of "nyabis" cultural integration with governance carried out by the kiai in the Salafiyah Islamic Boarding School Raudlatul Ulum Sumberwringin Jember. This study uses a research method with a qualitative approach to phenomenology. The results of this study indicate that "nyabis" in the world of Islamic boarding schools has an essential role in the life of santri. Nyabis activities are carried out to show respect and respect for fellow students who are more senior, scholars or teachers at Islamic boarding schools, as well as community leaders visiting Islamic boarding schools.